Non-Dynastic Elites of the Ruthenian (?) Origin in the Military Service of the Piasts of the End of the 12th – the First Half of the 14th Century. Some Anthroponymical Observations - Grabarczyk, Tadeusz; Kita, Jarosław; Pogońska-Pol, Magdalena; Voloshchuk, Myroslav; Agnieszka Gralak (Narzędzia wojny, 2023)
Extremely close inter-dynastic Ruthenian-Polish relations of the 10th–14th centuries were accompanied not only by the largest number of the bilateral marriages of the rulers, permanent military conflicts, peace treaties, the appearance of the compact communities of Ruthenians in the cities of the Piast dynasty or of Poles in Rus’, but also often by the military service to the neighboring dynasties. The presence of the outlined as the „Lyakhs” in the service of the Rurikids is well known. Our task was to find the analogues of the military service of single Ruthenians by the Piasts. According to the Latin identification „Ruthenus”, such persons could not be found during the mentioned period. However, the example of four representatives of the military nobility, bearers of the completely atypical for the possessions of the Polish dynasty names, deserves a special attention. There were Борис (Boris, Borissij, Borisius), in two cases Василь (Vasillus, Waysil, Waysszil, Waszil, Vazil, Woysil) and Дмитро (Dimitrius). In our opinion, most likely we are talking about the representatives of the non-dynastic elites of the Ruthenian origin in the first or second generations, who ended up in the service of the Silesian, Lesser Poland, or Masovian Princes due to the existing bilateral inter-dynastic relations, however – as a result of the matrimonial ties of the nobles of both countries.